Managing geomorphic values within Tasmanian plantations on karst terrain. Issue 3 (3rd July 2019) - Slee, A.; McIntosh, P.; Webb, J.; Sharples, C.; Williams, K.
ABSTRACT: The hazards associated with land use in karst terrain are widely recognised but those associated with forest operations on karst have received relatively little attention. The Tasmanian Forest Practices Code, first introduced in 1987, specifies that natural values in karst terrain are protected and managed during forest operations. Consequently, planning of operations on plantations in karst terrain requires detailed documentation and mapping of the karst features (chiefly sinkholes and caves) present. Planning by Forest Practices Officers, working with geoscientists at the Forest Practices Authority (FPA), has generally ensured that karst features have been avoided at planting, but because karst is an active process, prescriptions to protect karst in first rotations may need to be upgraded in Forest Practices Plans (FPPs) produced for later rotations. Experience gained in both pre-Code and post-Code plantations led the FPA to develop new guidelines for forest operations on karst. Instead of classifying sinkholes on their basis of their size and genesis, the guidelines classify them pragmatically into three categories—passive, active and recent—broadly related to perceived risk of further collapse and runoff-filtering capacity and apply appropriate management prescriptions for each category. Incorporation of these prescriptions into FPPs ensures risk-related management for karst features and reduces hazards for machinery operators and forest managers. The guidelines can be applied by foresters and forest planners trained in geomorphic processes and could be applied more broadly in karst terrain.